Dissection Course in Anatomy as Stimulus to Independent Research and to a Real Step into Medicine - Nikolenko, Vladimir; Oganesyan, Marine; Zakirov, Felix; Kudryashova, Valentina; Rizaeva, Nelly; Valiullina, Polina (Journal of Morphological Sciences, 2019)
Objectives In the recent years, many strategies in anatomy education have appeared. However, these innovations reduce the time students can spend on cadaver-based classes, which are considered to be an effective method of learning anatomy. The aim of the present research was to observe the advantages and features of dissection sessions in medical universities.Materials and Methods The comparative analysis of the academic performance of dissector (n = 30) and nondissector (n = 105) students and a survey questionnaire were conducted. The data was collected through the work of the Dissection Mastery School (DMS) of the Sechenov University, Moscow, Russia, between 2016 and 2018.Results The data analysis showed significant higher examination results in the dissectors cohort (p < 0.001) and a strong opinion about dissection as a good tool to improve anatomy knowledge (95% of responders). Apart from that, prosection is proven to have advantages in comparison with alternative learning approaches, according to researches performed by colleagues.Conclusion These data show that dissection still remains one of the most effective and beneficial methods of teaching anatomy in medical universities, and that it should be further integrated into the medical curriculum.
Keywords: anatomy; cross-sectional anatomy; dissection; medical education; methodology